Optimization of Landowning and Land Use: Contradictions and Solutions - М. V. Shchuryk (Статистика України, 2015)
Organization of landowning and land use in the agrarian sector of the Carpathian macroregion (Western Ukraine) is studied in the context of agrarian and land reforms. Critical assessment of the principles of privatizing and sharing the agricultural lands of the former collective and state agricultural farms is given. It is argued that ill-conceived transformation measures launched at the beginning of market economic reforms led to excessive fragmentation of lands, handing over land plots to ineffective owners and users, thus preventing from rise and development of small and medium agricultural enterprises. It is emphasized that the contradictions that the agrarian sector has to face when operating on the existing principles of landowning and land use cannot be overcome. Telling arguments are given to prove that the existing structure of owners and user of agricultural lands in the Carpathian macroregion is incapable to ensure high performance in terms of land use and preservation, improvement and protection of land plots and finding right solutions for ecological and social problems. It is argued that the largest flaw that triggered destructive tendencies in organization of the existing land farms is excessive and populist socialization instead of creating agricultural farms on rational and professional grounds, in conformity with market-based land relations. The flaw originates from mistakes and contradictions between economic and social components of land reform.